Biophysical Characterization of Type III Pantothenate Kinase (PanK) from Acinetobacter baumannii - Singla, Ankita; Sharma, Pradeep; Gupta, Akshita; Iqbal, Naseer; Rani, Chitra; Singh, T.P.; Sharma, Sujata (Protein and Peptide Letters, 2021)
Background: Type-III Pantothenate kinase from the multi drug resistant bacteria, Acinetobacter baumannii (AbPanK) catalyzes the first step of the essential Coenzyme A biosynthesis pathway. AbPanK is an attractive drug target against the bacteria since it is an essential enzyme and its structure is significantly different from the human PanK. Methods: AbPanK was cloned, expressed, purified and crystallized. A good quality single crystal was used for x-ray intensity data collection. Dynamic light scattering was done for calculating the hydrodynamic radii and its oligomeric nature in the solution. Binding studies of this protein with its two substrates, Pantothenate and ATP were done using spectrofluorometer. Results: Our results indicated that AbPanK shows a strong affinity with pantothenate with dissociation constant of 1.2 x 10- 8 M and moderate affinity towards ATP of 3.7x 10-3 M. This fact was further substantiated by the calculations of Km of both substrates using kinase assay kit. Dynamic light scattering studies have shown that it exists as homogenous solution with hydrodynamic radii corresponding to the molecular weight of 29.55 kDa. A low-resolution x-ray intensity data set was collected, which shows that AbPank crystallizes in P2 space group with cell dimensions of a= 165 Å, b= 260 Å, and, c= 197 Å and α= 90.0, β= 113.60, γ= 90.0. Discussion: Recombinant Pantothenate kinase from Acinetobacter baumannii was purified to homogeneity and crystallized. The enzyme exhibits very low sequence identity (28%) to other corresponding enzymes. Conclusion: The recombinant enzyme was active and its binding affinities with its substrates pantothenate and ATP have been studied. This information would be very useful while designing the inhibitors of this enzyme in order to fight bacterial infections associated to this pathogen.
Keywords: Acinetobacter baumannii